Recent Advances in the Analysis Full/Empty Capsid Ratio and Genome Integrity of Adeno-associated Virus (AAV) Gene Delivery Vectors - Hajba, Laszlo; Guttman, Andras (Current Molecular Medicine, 2020)
Adeno-associated virus (AAV) is one of the most promising viral gene delivery vectors with long-term gene expression and disease correction, featuring high efficiency and excellent safety in human clinical trials. During the production of AAV vectors, there are several quality control (QC) parameters that should be rigorously monitored to comply with clinical safety and efficacy. This review gives a short summary of the most frequently used AVV production and purification methods, focusing on the analytical techniques applied to determine the full/empty capsid ratio and the integrity of the encapsidated therapeutic DNA of the products.
Keywords: full/empty capsid ratio